Pengaruh Produksi Beras, Konsumsi Beras Dan Cadangan Devisa Terhadap Impor Beras Di Indonesia - Zaeroni, Rikho; Rustariyuni, Surya Dewi (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2016)
The agricultural sector is the primary sector and plays an important role in the national economy. One of the results of the agricultural sector is rice which is the staple food of Indonesian citizens. This study aimed to determine the effect of simultaneous and partial production, rice consumption and foreign exchange reserves to import rice in Indonesia, as well as to analyze the variables that influence most dominant to import rice in Indonesia-year period 2000-2014. Data analysis technique used is multiple linear regression. The results showed that simultaneous production variables, consumption and foreign exchange reserves have significantly influence the imports of rice in Indonesia in 2000-2014. Partially rice production variables and rice consumption did not affect the import of rice in Indonesia in 2000-2014. Variable foreign reserves significant have positive effect on imports of rice in Indonesia in 2000-2014.
Keywords: production, consumption of rice, foreign exchange reserves to import rice